Revision and phylogenetic analysis of Chilioediscelis (Hymenoptera: Colletidae) with descriptions of three new species - Willis, Erin; Packer, Laurence (Zootaxa, 2008)
The southern South American subgenus Chilioediscelis Toro and Moldenke is revised. The males and females of three new species, C. mirzamalae Willis & Packer, C. sardonyx Willis & Packer and C. penai Willis & Packer, are described. A key to species, distribution map and results of a phylogenetic analysis of the subgenus are provided. All character states used in phylogenetic analysis are either illustrated or references to figures of them are given.